“The Bitter Laughter”. When Parody Is a Moral and Affective Priming in Political Persuasion - D’Errico, Francesca; Poggi, Isabella (Frontiers in Psychology, 2016)
Research on socially aware systems requires fine-grained knowledge of the mechanisms of persuasion in order to promote civic knowledge and aware political participation. Within humour studies, political parody is generally considered a simple pleasant weapon for political evaluation , currently explained by referring to the so called “just a joke effect” (Nabi, 2007). Indeed the funny side of parody can induce positive emotions, but it also includes a discrediting act that sometimes produces a “bitter laughter”. The present study aims to understand the role played by negative and moral emotions aroused by parody. A parody is defined as a communicative behaviour (a discourse, text, body movement, song) that imitates a communicative behaviour or trait displayed by some Target by reproducing it in a distorted way, with the aim of making fun of the Target. Based on a socio-cognitive approach, a distinction is made between “surface” and “deep” parody (Poggi and D’Errico, 2013), with the former simply imitating behaviours actually displayed by the Target, and the latter implying a (humorous) re-categorization of the Target. The paper studies the effect of these two different types of parody on persuasion processes. Results show that the deep parody, as opposed to surface parody, triggers more negative emotions, and in particular indignation, that in turn lead to more negative evaluations of the Target. Moreover, the moral priming of parody is influenced by the Target politician’s gender.